Políticas de austeridade fiscal e impactos acadêmicos na gestão do Centro de Ciências Agrárias da UFPB, no período de 2014 a 2018 - Carvalho, Carlos Eduardo Valdivino de (2022)
In the scope of neoliberal policies and their relationship with the funding of higher education, this study aims to analyze the Fiscal Austerity Policies in the Discretionary Budget of the Center for Agricultural Sciences (CCA), from UFPB, from 2014 to 2018, and their impacts on academic scholarships and financial aid to promote teaching, research, extension and undergraduate student assistance activities, which are financed by the discretionary budget of the Campus. In this sense, an analysis was carried out of the discretionary budget allocations directed to the Center and its historical variation in the delimited period, as well as indicators related to the amount of scholarships and grants granted in the period. Data for analysis were collected through documents made available via the Access to Information Law, SIPAC-UFPB, electronic queries to the Federal Budget Panel – SIOP, and e-mails to specific sectors of the university. Information and concepts obtained from leading authors in their fields were also used, specialized in topics such as “financing of higher education”, “State and Keynesianism” and “neoliberalism”, as well as official documents from international and Brazilian institutions, such as the Banco Organization for Economic Cooperation and Development, UFPB Management Reports, UFPB Institutional Development Plans, and the document “UFPB in numbers.” Research analysis showed that, with the advent of fiscal austerity policies, the Center of Agrarian Sciences had a process of accentuated precariousness in the budget for Other Current and Capital Expenses, revealing an even more critical situation when considering only the amounts actually paid, affecting the number of academic scholarships and financial aid granted, in amounts and different periods. It is the neoliberal project for higher education, subject to the directives of international and characterized by restrictions on public funding, which makes it impossible to maintain and develop quality education. An ideology that seeks the defection of the State in its social, political and economic responsibilities.